The Penetration of Green Innovation on Firm Performance: Effects of Absorptive Capacity and Managerial Environmental Concern - Min Xue (Sustainability, 2019)
Under the background of environmental sustainability, it is of great significance to investigate how green innovation influences firm performance dimensions in emerging economies. Explicitly, the interaction effects of absorptive capacity (AC) and managerial environmental concern (MEC) on the correlation between green innovation and firm performance dimensions must be explored. Our data were obtained through a questionnaire survey from 253 companies operating in China. Using hierarchical linear modeling (HLM), we found that (1) green innovation has a robustly positive effect on firm performance dimensions (operational, financial and environmental), and (2) absorptive capacity and managerial environmental concern can positively affect the correlation between green innovation and firm performance dimensions. Our results illustrate the integrating effects of absorptive capacity, managerial environmental concern, green innovation and firm performance dimensions.